Unpacking Professionalism and Capacity Building in Early Childhood Education: A Phenomenological Approach - Salamah, Mar’atus (Generasi: Jurnal Pendidikan Anak Usia Dini, 2024)
Backround: Professional development and capacity building are essential for improving quality, equity, and outcomes in early childhood education globally. As systems strive to enhance the skills and knowledge of educators, understanding the lived experiences of early childhood professionals is crucial for designing effective programs. Objective: This study aims to explore the experiences of 58 early childhood professionals from Australia, Canada, and Taiwan who participated in systematic professional development and capacity-building initiatives. The focus is on understanding how these initiatives shape educators' professional identities, growth, and pedagogical practices. Method: A phenomenological approach was employed, utilizing van Manen's hermeneutic phenomenological methodology. Data were collected over 14 months through in-depth semi-structured interviews, focus group discussions, professional portfolios, and reflective journals. Findings and Impications: The study identified four key themes: Conceptualizing Professionalism (navigating evolving professional identities), Capacity Building Strategies (mentoring, technology, and communities of practice), Barriers and Facilitators (time, funding, organizational support), and Transformation and Impact (improvements in pedagogy, leadership, and organizational culture). Conclusion: The findings highlight the importance of professional development in fostering identity transformation, critical reflection, and systemic change. Organizational culture, leadership support, and collaborative networks were crucial for effective capacity building. The study underscores gaps in mental health support and inclusive practices, offering insights for future professional development and policy frameworks in early childhood education.